A Hot-Polymer Fiber Fabry–Perot Interferometer Anemometer for Sensing Airflow - Lee, Cheng-Ling; Liu, Kai-Wen; Luo, Shi-Hong; Wu, Meng-Shan; Ma, Chao-Tsung (Sensors (Basel, Switzerland), 2017)
This work proposes the first hot-polymer fiber Fabry–Perot interferometer (HPFFPI) anemometer for sensing airflow. The proposed HPFFPI is based on a single-mode fiber (SMF) endface that is attached to a UV-cured polymer to form an ultracompact fiber Fabry–Perot microcavity. The proposed polymer microcavity was heated using a low-cost chip resistor with a controllable dc driving power to achieve a desired polymer’s steady-state temperature (T) that exceeds the T of the surrounding environment. The polymer is highly sensitive to variations of T with high repeatability. When the hot polymer was cooled by the measured flowing air, the wavelength fringes of its optical spectra shifted. The HPFFPI anemometers have been experimentally evaluated for different cavity lengths and heating power values. Experimental results demonstrate that the proposed HPFFPI responses well in terms of airflow measurement. A high sensitivity of 1.139 nm/(m/s) and a good resolution of 0.0088 m/s over the 0~2.54 m/s range of airflow were achieved with a cavity length of 10 μm and a heating power of 0.402 W.